Family networks and refugees’ health conditions. A picture from Italian informal settlements - Mendola, Daria; Busetta, Annalisa (Migration Letters, 2021)
While the relationships between social networks and health are widely acknowledged in the literature, few of these studies have covered the population of refugees living in makeshift camps. In our analysis of a nationally representative Italian survey of individuals living in informal settlements, we find that many had weak family relations: only 10 per cent had one or more family members in their settlement. The paper analyses the effects of individual social network on two measures of health, and finds that the refugees’ health conditions were associated with both their personal characteristics and the characteristics of the settlement. The results show that more than 50 per cent of these foreign nationals recently had health problems, and that those with no family members in the settlement had significantly higher chances of both being in bad or very bad health and having experienced a health problem in the last month.